1994
DOI: 10.1038/bjc.1994.298
|View full text |Cite
|
Sign up to set email alerts
|

Progression and survival in prostatic adenocarcinoma: a comparison of clinical stage, Gleason grade, S-phase fraction and DNA ploidy

Abstract: S_ry Clinical data were reviewed in 325 patients with prostatic adenocarcinoma followed up for a mean of 13 years. Paraffin-embedded tumour biopsy specimens from the primary tumours were available for flow cytometry (FCM) in 273 cases. Intra-tumour heterogeneity in DNA index (DI) was found in 4% of the tumours (54 cases were analysed). S-phase fraction (SPF) and DNA ploidy were significantly interrelated. Aneuploidy and high SPF were significantly related to both a high T category and high Gleason score. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
2
29
0
1
Order By: Relevance
“…These results suggest that tumours with reduced α-catenin expression rapidly progress locally into invasive disease. It is obvious that the metastatic potential of prostate tumours is not dependent on cell adhesion factors alone, and many other factors including the host response are involved (Vesalainen et al, 1994). In alignment with our notion, the relationship between α-catenin expression and tumour spread has been reported previously in prostate cancer (Richmond et al, 1997) and in tumours of the urinary tract (Shimazui et al, 1996).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results suggest that tumours with reduced α-catenin expression rapidly progress locally into invasive disease. It is obvious that the metastatic potential of prostate tumours is not dependent on cell adhesion factors alone, and many other factors including the host response are involved (Vesalainen et al, 1994). In alignment with our notion, the relationship between α-catenin expression and tumour spread has been reported previously in prostate cancer (Richmond et al, 1997) and in tumours of the urinary tract (Shimazui et al, 1996).…”
Section: Discussionsupporting
confidence: 74%
“…The volume corrected mitotic index method (M/V index) was used, which expresses the number of mitotic figures/square millimetre of tumour tissue in the section (Vesalainen et al, 1995). The results of flow cytometry have been reported in detail previously (Vesalainen et al, 1994). DNA index was available in 182/215 (85%) of cases and S phase fraction in 175/215 (81%) of cases.…”
Section: Histological Methods and Flow Cytometrymentioning
confidence: 99%
“…The increase in AR in low-grade tumors as measured by immunohistochemistry is not quantitative and is a better measure of percentage 29 rather than intensity of staining. The fact that AR density is related to S-phase fraction, which has been shown in prior studies [32][33][34][35][36] to be associated with poor prognostic features and outcome, may indicate that the significance of AR density may be different from that of the percentage of AR-positive cells. For example, the amount of ARs per cell may be increased due to the presence of nonfunctioning AR with upregulation, a mutation leading to sensitivity of AR to other substrates or simply increased AR due to androgenic stimulation leading to more division.…”
Section: Discussionmentioning
confidence: 99%
“…22 The additional advantage to this technique is the ability to measure S-phase fraction and ploidy , which have been found to have prognostic value in several publications. [32][33][34][35][36] ARs may stimulate proliferation through their mechanism of action. However, it is not known whether high AR density correlates with a higher S-phase fraction, with its adverse prognostic implications.…”
Section: Introductionmentioning
confidence: 99%
“…• 8 level 1b studies reported a significant correlation of DNAcytometric features with histologically proven cancer spread beyond the capsule as detected after radical prostatectomy [167][168][169][170][171][172][173][174]. 4 of them document a significant improvement of diagnostic accuracy concerning the prediction of organ confinement by DNA-ploidy features over Gleason-score alone ( Table 3).…”
Section: Methodologically Sufficient Papersmentioning
confidence: 99%